Upstairs-Downstairs Active Learning and Compelling Interpretation. Issue 1 (March 2014) - Sinclair, Janet
The context for this paper is Stansted Park, an historic Edwardian house in southern England, given by the 10th Earl of Bessborough (d. 1993) to Stansted Park Foundation which now owns, conserves and administers the house, its moveable property and furnishings, and forested estate. The house has been open to the public since the 1980s but is no longer lived in by the family. This article describes differing yet complementary methods of interpretation, with specific examples of activities undertaken to fully involved and engage visitors of all ages and abilities through real life stories, while protecting the collections. Firstly, it discusses where, why and how collection items, their owners and their stories are presented. Secondly, how this engenders and enables an informal self-directed learning relationship between visitors and objects. Finally, more formal learning structures around school-age visitor activities are described, and outcome is documented by visitor feedback. The author is a member of the Attingham Society 1 and Curator at Stansted Park, where she was House Manager 2008–12. During this period Stansted Park won two Quality Badges for Learning Outside the Classroom (LOtC) and was highly commended as best Small Attraction in South East England. Each award recognized high levels of active learning, accessibility and sustainable interpretation, balanced by the conservation issues. 2